Early post-surgical rehabilitation and functional outcomes of a traumatic ulnar nerve injury: a pediatric case report - Fulceri, Federica; Marinelli, Chiara; Ghelarducci, Giulia; Nucci, Anna Maria; Poggetti, Andrea; Ryskalin, Larisa; Gesi, Marco (Frontiers in Neurology, 2024)
Background Peripheral nerve injuries (PNIs) of the upper limb are very common events within the pediatric population, especially following soft tissue trauma and bone fractures. Symptoms of brachial plexus nerve injuries can differ considerably depending on the site and severity of injury. Compared to median and radial nerves, the ulnar nerve (UN) is the most frequently and severely injured nerve of the upper extremity. Indeed, due to its peculiar anatomical path, the UN is known to be particularly vulnerable to traumatic injuries, which result in pain and substantial motor and sensory disabilities of the forearm and hand. Therefore, timely and appropriate postoperative management of UN lesions is crucial to avoid permanent sensorymotor deficits and claw hand deformities leading to lifelong impairments. Nevertheless, the literature regarding the rehabilitation following PNIs is limited and lacks clear evidence regarding a solid treatment algorithm for the management of UN lesions that ensures full functional recovery. Case presentation The patient is a 11-year-old child who experienced left-hand pain, stiffness, and disability secondary to a domestic accident. The traumatic UN lesion occurred about 8 cm proximal to Guyon’s canal and it was surgically treated with termino-terminal (end-to-end) neurorrhaphy. One month after surgery, the patient underwent multimodal rehabilitative protocol and both subjective and functional measurements were recorded at baseline (T0) and at 3- (T1) and 5-month (T2) follow-up. At the end of the rehabilitation protocol, the patient achieved substantial reduction in pain and improvement in quality of life. Of considerable interest, the patient regained a complete functional recovery with satisfactory handgrip and pinch functions in addition with a decrease of disability in activities of daily living. Conclusion A timely and intensive rehabilitative intervention done by qualified hand therapist with previous training in the rehabilitation of upper limb neuromuscular disorders is pivotal to achieve a stable and optimal functional recovery of the hand, while preventing the onset of deformities, in patients with peripheral nerve injuries of the upper limb.